Evaluation the Fractions from Extract Ethanol Psidium Guajava Leaves on Total Phenolic Content, Antioxidant Activity and Its Antibacterial Activity of Staphylococcus Aureus. - Mustofa Ahda (Journal of Global Pharma Technology, 2019)
Objective: The aims of this research to find the potential extract and fraction from ethanol extract of Psidium Guajava L for natural antioxidant and antibacterial. The extract and fraction of Psidium Guajava L was analyzed the phenol total content, antioxidant activity and its antibacterial. Methods: The ethanol extract of Psidium Guajava L was extraxted using n hexane, ethyl acetate and water. The all fraction and ethanol extract of Psidium Guajava L was determined the scavenging activity, penolic compound. The scavenging activity was determined by DPPH method. The phenolic compound was determined with Folin-Ciocalteu method. Results: The result of this research showed that the fraction of ethyl acetate has highest antioxidant activity with the value is 9.07 µg/mL. It is also supported by the result of screening phytochemical that ethyl acetate fraction contains mostly complete of chemical substances. However, The highest total phenol content was found in water fraction with phenolic content of 26%. The anbacterial activity of ethanol 96% extract of Psidium guajava leaves and ethyl acetate fraction have a highly activity to inhibit the Staphylococcus Aureus. Conclusion: The fraction of ethyl acetate has a highest of antioxidant activity, although it doesn’t have highest of total phenolic content. The highest of total fenolic content from water fraction is 26%. The scheme of antibacterial activities potential of Guajava extracts are ethanol 96% extract = ethyl acetate fraction > n-hexane fraction = water fraction